Evaluation of Cathodic Protection Potential Criteria for Stainless Steel and Carbon Steel Couple in Seawater Environment - Ghazali, Ahmad Farhan Izzuddin (IRC, 2021)
Cathodic protection is commonly used method in mitigating corrosion. The method relies on polarizing the structure to a protection potential set by industrial standard.